Lady of Palenque : flower of Bacal - Kirwan, Anna (The royal diaries, 2004)
In 749, the Maya princess Green Jay, of the Kingdom of Bacal, writes in her diary about her arduous journey to Xukpip to meet King Fire Keeper, her future husband.